(untitled) (Bangladesh Journal of Medical Science, 2013)
Background: Garo is one of the largest indigenous communities of Bangladesh. Adolescence is a golden period of time for nutritional promotion. Adolescent nutrition did not receive adequate attention in Bangladesh. Tribal people like the Garo are even more unaware about the importance of adolescent nutrition. Objectives: To find out physical growth as well as nutritional status among adolescent Garo children in Sherpur district on the basis of anthropometric indices. Methods and materials: This cross sectional descriptive study was conducted among 384 adolescent Garo children (boys and girls) aged 10- 18 years. A structured pre-tested questionnaire and a checklist were used to collect data through interview. Anthropometric survey of randomly selected adolescent was carried out and compared against the NCHS/WHO reference indicators such as BMI-for-age, Height-for-age and Weight-for-age. Standard methods were applied to measure the height and weight of the adolescent and BMI was calculated. Associations of nutritional status with socio-economic status, maternal working status, family type and family size were determined. Results: In most of the age groups it is notable that the mean height and weight of both boys and girls were lower than the WHO/NCHS standards. The prevalence of thinness, stunting and underweighting was 49.74%, 15.1% and 7.29% respectively. Conclusions: Significant association between malnutrition and socio-economic parameters was observed. So socio-economic status, maternal working status, family type and family size are important determinants of nutritional status of adolescent. Therefore, comprehensive programmes are required to be undertaken for the overall nutritional development of the Garo population with special focus on the adolescents. Bangladesh Journal of Medical Science Vol. 12 No. 03 July 13 Page 269-275 DOI: http://dx.doi.org/10.3329/bjms.v12i3.15423